Thyroid Dysfunction in the Elderly with Hearth Failure - Gordana MIHAJLOVIC; Miljanka VUKSANOVIC; Nebojsa DESPOTOVIC; Maja NIKOLIC-DESPOTOVIC; Predrag ERCEG; Dragoslav P. MILOSEVIC; Tomislav JOVANOVIC (Tehran University of Medical Sciences, 2017)
Thyroid Dysfunction in the Elderly with Hearth Failure